Calcitriol Prevents Neuroinflammation and Reduces Blood-Brain Barrier Disruption and Local Macrophage/Microglia Activation - de Oliveira, Larissa Ragozo Cardoso; Mimura, Luiza Ayumi Nishiyama; Fraga-Silva, Thais Fernanda de Campos; Ishikawa, Larissa Lumi Watanabe; Fernandes, Ana Angélica Henrique; Zorzella-Pezavento, Sofia Fernanda Gonçalves; Sartori, Alexandrina (Frontiers in Pharmacology, 2020)
Multiple sclerosis (MS) is a progressive disease of the central nervous system (CNS) that involves damage to the myelin sheath surrounding axons. MS therapy is based on immunomodulatory drugs that reduce disease recurrence and severity. Vitamin D is a hormone whose immunomodulatory ability has been widely demonstrated, including in experimental autoimmune encephalomyelitis (EAE), which is an animal model of CNS inflammation. In this study, we evaluated the potential of very early intervention with the active form of vitamin D (1,25-dihydroxyvitamin D3) to control neuroinflammation during EAE development. EAE was induced in C57BL/6J mice and 1,25-dihydroxyvitamin D3 administration began 1 day after disease induction. This procedure decreased prevalence, clinical score, inflammation, and demyelination. It also reduced MHCII expression in macrophages and microglia as well as the level of oxidative stress and mRNA expression for NLRP3, caspase-1, and IL-1β at the CNS. Otherwise, mRNA expression for ZO-1 increased at the lumbar spinal cord. These effects were accompanied by the stabilization of blood-spinal cord barrier permeability. The results of this study indicate that early intervention with 1,25-dihydroxyvitamin D3 can control the neuroinflammatory process that is the hallmark of EAE and MS immunopathogenesis and should thus be explored as an adjunct therapy for MS patients.